Smoking status and factors influencing smoking cessation among primary school parents: A cross-sectional study (Annals of Medical Research, 2024)
Aim: This study aims to determine smoking status among primary school parents and identify factors influencing smoking cessation. Additionally, the study seeks to increase awareness about the transtheoretical model and examine its role in the smoking cessation process.Materials and Methods: The study was conducted with 2,354 parents of students from a primary school in Konya. Participants completed surveys assessing smoking status, attitudes towards quitting, and levels of awareness. Factors related to smoking status, including age, gender, education level, occupation, and alcohol use, were analyzed. Smokers quit attempts were associated with the stages of the transtheoretical model, and whether they sought professional help was evaluated.Results: Of the participants, 33.1% (n=780) were smokers. The average age of smokers was 36.6±4.61, and the frequency of smoking was higher among men than women. 39% of the participants were low-level smokers. Significant associations were observed between smoking status and factors such as age, gender, education level, occupation, and alcohol use (p
Keywords: Smoking; Smoking cessation; Primary school; Transteorical model